Critique of the just war in Thomas Aquinas and Grotius - Tooke, Joan D. (The University of Edinburgh, 1962)
Warfare is a complex phenomenon. There have been sufficient wars in history to suggest that fighting is either a normal human activity or an endemic human disease which men perpetuate although they consciously do not desire it. It has become a habit of humanity and closely woven into civilization it has been condemned as butchery and upheld as a gallant and gentlemanly enterprise. War and the fear of war are shadows in the background of life yet close within one's own instincts; war signifies the safety of defence as well as the danger of destruction. It is indeed paradoxical. Whatever the perfect Christian teaching on participation in warfare, Christians have to live in and confront a largely non-Christian world. To preach perfection and try to persuade men to accept it is not enough, and the realist who attempts to make a dangerous situation safe must not be underestimated. Whether peace on this earth will ever come about without the spiritual maturity of the human race might be a good subject for debate between lawyers and theologians. The claim that the way of Christian love is the only true and sure way even in the midst of human wickedness is one that has been sometimes perhaps too summarily dismissed as ineffective and a little nebulous. On the other hand it may be because law is confessedly such a secular activity that many Christians have perhaps undervalued and made insufficient use of the contribution made by international lawyers who, by building up a tradition of faith in reasonable and just dealings between nations and a technique of dealing with dangerous situations and disputes, have already done much to prevent and assuage outbreaks of hostilities. Lawyers have above all experience of the world and wisdom in accommodating affairs to what is humanly possible. The founders of international law were professedly Christian, as are many international lawyers in the modern world, and although the foundation of modem international law, which has to be acceptable to all, including non Christian states, is no longer professedly Christian, this does not mean that its work is less vital or less the concern of Christians and churches. Although in some matters there may be disagreement and the need for delicate discimination as to the grounds and degree A of co-ordination, there should be considerable mutual appreciation and co-operation between theologians and lawyers. Both must have to acknowledge uncertainties and inadequacies in their positions, and some understanding of these might be gained by looking into the work of one who has been acclaimed as the 'Father of International Law' and whose labours were inspired by Christian faith. Both international law. Christian pacifism and non-violent resistance are pioneer movements but progress has often come about through ideals which have started in the defeatist position of being the possession of a minority. It does not need prophetic insight to see that both an international legal system which goes a tremendously long way - as far as it believes safe - in saying no to war, and the Christian who believes that he must keep fresh the ideal of an absolute refusal, have a part to play in its final conquest, and that they have history on their side. Neither is guaranteed immediate practical success, but it is imperative that though they may disagree at some vital points, they should respect and as far as they can support each other. Law has done much to protect the right of conscience in some though not yet in all states. If we consider human nature in its wholeness it may indeed seem realistic to believe that it needs tremendous restraints. The extreme Christian position may seem remote from these realities but if we consider the present international situation it does not seem so unrealistic to believe that finally an absolute love may alone be able to conquer the conflict. In the last war death and destruction were wrought at both Coventry and Kiel by the natural instincts of both aggression and defence. In the Chapel of Unity in the new cathedral at Coventry aid in the church of St Nicholas at Kiel, relics of the destruction sent from the enemy countries witness to a measure of reconeiliation which has resulted from the desecration. Man's spirit can survive the worst of human evils but may be able to do so 'only by remembering that the true man is not one on the warpath for revenge. The true man is One on a cross, forgiving ever to the last deadly insult.
A critique of the just war in Thomas Aquinas and Grotius